Broadband optical nonlinearity of zeolitic imidazolate framework-8 (ZIF-8) for ultrafast photonics. Issue 28 (28th June 2021) - Dong, Li; Chu, Hongwei; Li, Ying; Zhao, Shengzhi; Li, Dechun
Abstract : Zeolitic imidazolate frameworks (ZIFs) show extraordinary potential in the domains of fundamental research and miscellaneous technology applications. Abstract : Zeolitic imidazolate frameworks (ZIFs) show extraordinary potential in the domains of fundamental research and miscellaneous technology applications. Herein, ZIF-8 nanomaterials were fabricated successfully and their broadband linear and nonlinear optical properties were determined by UV-vis-NIR and open-aperture/closed-aperture (OA/CA) Z-scan techniques. The results illustrated the eminent broadband nonlinear absorption properties of ZIF-8, which were further manifested by broadband passively Q-switched (PQS) lasers operating from 1 to 2 μm with ZIF-8 as the saturable absorber. Moreover, ZIF-8 was integrated into a ytterbium-doped fiber laser (YDFL) for the first time and a stable ultrafast dissipation soliton mode-locking operation with a pulse width of 21.3 ps was realized. Given the high thermochemical stability, excellent broadband nonlinear optical (NLO) characteristics and remarkable ultrafast mode-locking capability, the current main research lays the foundation for advanced ultrafast photonics based on diverse metal–organic frameworks (MOFs).